4CPS-060 Pharmaceutical role in an antimicrobial stewardship programme. (2nd March 2018) - Barcelo, J; Fernández-Sala, X; Echeverría-Esnal, D; Ferrández, O; Luque, S; Grau, S
Abstract : Background: The emergence of multidrug-resistant microorganisms is a serious threat to global public health that requires action. Thus, the implementation of antimicrobial stewardship programmes aims to optimise antibiotic prescription and prevent antimicrobial resistance. Although these programmes are multidisciplinary, there is a lack of data about the specific role of pharmacists. Purpose: To describe pharmacists' activity in an antimicrobial stewardship team. Material and methods: Retrospective descriptive study performed in a 400-bed tertiary hospital. Data from all pharmaceutical interventions referring to any antimicrobial prescription registered between January 2014 and December 2015 were collected. Vancomycin- and aminoglycosides-related interventions were excluded as they belong to another intervention area. Antimicrobial prescriptions were reviewed every day through an electronic prescription program. Pharmaceutical interventions were gathered and registered in six different groups: renal impairment adjustment, dose adjustment, frequency adjustment, drug-interactions and miscellaneous (adverse events, therapeutic drug monitoring, monitoring of biochemical parameters…). Acceptance by physicians was also evaluated. Categorical values were presented in percentages. Results: A total of 1026 interventions were recorded. The 26.1% were renal impairment adjustments; 24.7% dose adjustments; 17.3% miscellaneous; 13.1% related to antimicrobial-spectrum; 9.7% interactions; and 9.2% frequency adjustments. From 1026 interventions, 80.4% were accepted, 11.6% rejected and 8 not evaluable. Conclusion: Adjustments due to renal impairment and dose adjustments were the main actions performed. Interestingly, a 13.1% of interventions were related to the antimicrobial-spectrum, mainly in antibiotics of high ecological impact. Overall, recommendations by pharmacists were highly accepted among physicians. These data highlight the important role of hospital pharmacists in antimicrobial stewardship programmes. No conflict of interest